-3+3x=4(x-3)+7

Simple and best practice solution for -3+3x=4(x-3)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+3x=4(x-3)+7 equation:


Simplifying
-3 + 3x = 4(x + -3) + 7

Reorder the terms:
-3 + 3x = 4(-3 + x) + 7
-3 + 3x = (-3 * 4 + x * 4) + 7
-3 + 3x = (-12 + 4x) + 7

Reorder the terms:
-3 + 3x = -12 + 7 + 4x

Combine like terms: -12 + 7 = -5
-3 + 3x = -5 + 4x

Solving
-3 + 3x = -5 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3 + 3x + -4x = -5 + 4x + -4x

Combine like terms: 3x + -4x = -1x
-3 + -1x = -5 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + -1x = -5 + 0
-3 + -1x = -5

Add '3' to each side of the equation.
-3 + 3 + -1x = -5 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = -5 + 3
-1x = -5 + 3

Combine like terms: -5 + 3 = -2
-1x = -2

Divide each side by '-1'.
x = 2

Simplifying
x = 2

See similar equations:

| 3x+9+30=105 | | 4x-20x=24 | | 0.5x-1.5=-0.4x-3.6 | | (2×-3)/4=9 | | 30+2x+9+x=180 | | -1/7x=-9 | | 2(x+3)-3=88-3x | | -3+5(m-5)=-20+6m | | 0.5x-1.5=0.4x-3.6 | | y-9=-1/7x | | 103.5=9(m+3.9) | | 4-8x=3(-7x-3) | | 3x-251=1189 | | 75+33x+9=180 | | 16x-23=57 | | 2982=42(p+20) | | 105+105+x=180 | | 4xy+2b-(3xy)-5b= | | 3x+9+x+x=180 | | 3x+20=2x-40+2x+20 | | -3+8m=11-4-2m | | 15a+5b=255 | | 736=4(x+17) | | y+(-19)= | | 3x+9+30=180 | | 2(-7k-3)+9= | | 2-144x^2= | | 7x+3y+9=0 | | -13.00+2.00=11.00 | | -6(7+2m)-8m= | | 3x/8=19 | | 2x+5=x+5+2x-70 |

Equations solver categories